Effect of Bypass Fat and Minerals Supplementation during Transitional Period on Plasma Levels of Thyroid Hormones, Metabolites and Postpartum Fertility in Crossbred Cows - Theodore, V.K.; Panchal, M.T.; Dhami, A.J.; Parmar, S.C.; Bhanderi, B.B.; Chaudhary , Sandhya (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Twenty healthy advanced pregnant crossbred (HF x K) cows of 2-4 parity were included in the study from 2 weeks prepartum to 8 weeks postpartum. They were equally divided in to control (routine farm feeding-RFF) and treatment (RFF plus area specific multi-minerals @ 50 g/h/d and bypass fat @ 100-200 g/h/d) groups to evaluate the effect of bypass fat and minerals supplementation on plasma metabolites and hormonal profile and postpartum fertility. The plasma levels of T3 increased (P<0.01) on the day of calving and then abruptly dropped till day 14 postpartum as compared to levels at other periods, while T4 decreased (P<0.05) consistently throughout the study period particularly in control group. However, the influence of nutritional supplementation was found to be non-significant on both these hormones. The blood glucose levels were at peak concurrent to highest plasma cortisol on the day of calving. The cows under supplemented group had significantly (p<0.01) higher mean blood glucose (64.51±3.10 vs 59.13±3.06 mg/dl) and cortisol (16.19±2.51vs 11.23±1.34 ng/ml)than the control cows. The mean plasma levels of NEFA increased from day 14 prepartum to the highest (p<0.01) on the day of calving and thereafter reduced in postpartum days in both the groups with significantly higher mean value in supplemented than control group (0.58±0.09 vs 0.47±0.07 mmol/l). The prepartum plasma BHBA also increased as parturition approached, continued to increase further in the early postpartum period to reach a peak (1.21±0.09 and 0.87±0.04 mmol/l for control and treatment group) (p<0.01) on day 14, and thereafter decreased. In general, the plasma NEFA, BHBA, cortisol and glucose levels were found to be higher in the cows of nutrient supplemented group which had lesser time intervals for expressing first postpartum estrus and service period with better pregnancy rate. Thus the nutrient supplementation during transition period was beneficial in maintaining energy status of the cows and improved reproductive performance postpartum.